Le ginseng d’Amérique : un lien entre les deux Indes, entre curiosité et science - Andreas Motsch (Etudes Epistémè)
Following a suggestion by Father Jartoux, who introduced ginseng in Europe in 1713, the missionary Joseph-François Lafitau discovered in 1716 that there was also ginseng in New France. His discovery was initially contested by members of the French Academy of Sciences who claimed that it was not ginseng but another plant. In 1718 Lafitau published a Mémoire [. . .] concernant la précieuse plante du Ginseng in which he gave a summary of what was known about ginseng and refuted the arguments of his critics. While the Academy was concerned with proper botanical classification, the confusion was readily clarified and Lafitau’s discovery of ginseng in North America gave rise to a lucrative market for the root that was even exported to Asia. This article offers an interpretation of the Memoire on ginseng by Joseph-François Lafitau in its historical context by linking its epistemological and methodological aspects to the author’s worldview and his self‑understanding as a missionary. Beyond aspects of botanical science, the article discusses the influence of the humanistic traditions of antiquarianism and curio collections, suggesting a methodological parallel between the Mémoire and Lafitau’s Mœurs des sauvages amériquains comparées au mœurs des premiers temps (1724). The discovery of ginseng is contextualized within the larger framework of geographic exploration and particular attention is paid to the uncertainties surrounding the discovery of America in relation to Asia and a possible land bridge between both continents. The presence of ginseng on both continents strongly supports such a hypothesis and a landbridge supports in turn the idea of Eurasian origins of Native Americans. While Lafitau’s Mœurs argues for the unity of mankind rooted in a common origin, the Mémoire addresses the question of the unity of creation through a demonstration in natural history.